FENOLOGIA DO ALGODOEIRO EM FUNÇÃO DA APLICAÇÃO DE DOSES DE P ENERGETIC® - GREITER, Luiz Mateus Gonçalves; COSTA, Victor Souza; LOPES, Fernando de Souza; MALDONADO, Eduardo da Cunha; SILVA, Pablo Rozo; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-